A commentary on the judgment of the Supreme Administrative Court 5th May 2016, II FSK 3354/15. A statement under penalty of perjury in tax returns - Bernat, Rafał (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
In this case, the court expressed its support for the introduction of the statement under penalty of perjury by the Municipal Council in the tax return without legal grounds for such a clause. According to the commentator, the analysed judgment contains no logical justification and the introduction of a statement of this content is contrary to the principle of the rule of law implemented in the procedure of tax. As a result of the research it was assumed that penal-fiscal re-sponsibility comes under the law in relation to certain documents and the introduction of a statement as groundless does not constitute “awkwardness” body but a deliberate action aimed at obtaining relevant information from the taxpayer that would not be willing to submit it if not penalty of perjury or penal-fiscal responsibility.